Pengembangan Media Pembelajaran Interaktif: Pengembangan Media Pembelajaran Interaktif Powerpoint Berbasis Classpoint pada Materi Matematika SMP - Azmi, Syahrul Azmi; Junaidi, Junaidi; Sripatmi, Sripatmi; wahidaturrahmi, wahidaturrahmi (FKIP Universitas Mataram, 2024)
The purpose of this research is to develop interactive learning media based on the Classpoint website that is feasible and practical to use in mathematics learning. This research is a development study using the 4D model, which consists of Define, Design, Development, and Disseminate. Data collection in this study is based on the validation results of instruments conducted by experts and teachers to assess the practicality of the media. The instruments used in this research include product evaluation instruments, covering valid (feasible) and practical aspects. The developed media is a PowerPoint learning media integrated with Classpoint, which can be operated online with a specific code. The results of the media development obtained an interactive learning media based on Classpoint that is valid (feasible) with a validation score of 0.9 and practical with a percentage of 90.8%.